Literature Review: Determinants of Patient Loyalty in Using Health Services - Sigit Eko Prasetyo; Dyah Wiji Puspita Sari; Iwan Ardian; Muh. Abdurrouf (GLOBAL HEALTH SCIENCE GROUP, 2025)
Patient loyalty is an important indicator of the success of a healthcare facility. Building patient loyalty is not an easy task. Many factors influence a patient's decision to remain loyal to a healthcare facility. Objective: This study aims to identify and analyze various factors that influence patient loyalty in health services. Methods: This research uses a literature study approach by reviewing national and international articles published in the period 2020-2024. The articles selected were limited to scientific publications available in full-text format and freely accessible. Literature sources were obtained from three main databases, namely Google Scholar, PubMed, and SciSpace. The search strategy was carried out using keywords based on the PICO (Population, Intervention, Comparison, Outcome) framework, such as “health services”, “factors” and patient loyalty”, resulting in 615 articles. The process of analyzing articles using PRISMA, searching and filtering journal articles began by identifying 615 articles from three main databases, Google Scholar (401 articles), PubMed (7 articles), and SciSpace (207 articles). At the initial stage, duplicate articles were eliminated, and the number of articles remaining after this screening was 107. In the screening process from this stage, 84 articles were excluded because they did not meet the predetermined criteria, so only 23 articles entered the next stage. At the eligibility stage, further selection was carried out by considering the inclusion and exclusion criteria. Of the 23 articles screened, 13 did not meet the criteria and were excluded from the selection process. In the end, only 10 articles met all the requirements and were included in the further review stage. Results: Analysis of the literature review patient loyalty in using health services is influenced by factors of service quality, price, communication, and trust.